Weathering the storm: why was there no Arab uprising in Algeria?. Issue 6 (19th September 2017) - Del Panta, Gianni
ABSTRACT: This article re-opens the discussion of why there was "no Arab Uprising in Algeria." After critically reviewing previous findings, the paper suggests that the stability of the Algerian regime was mainly a result of the non-formation of a cross-class and cross-ideological coalition. Splitting this hypothesis into its two main parts, it will be shown, first, that the working class was the missing element. Two factors explain this: (a) the numerical and strategic marginalization of productive workers – in turn, an effect of the process of de-industrialization that hit the country from the late 1980s onwards; and (b) the presence of an aristocracy of labour in the hydrocarbon sector, from which a tiny minority of workers produced an overwhelming amount of wealth. Secondly, the enduring distrust among opposition groups – a direct legacy of the still-too-recent civil war, as well as an effect of the specific institutional environment that developed from the mid 1990s onwards – prevented the establishment of a "negative coalition" through which all opposition forces could jointly mobilize against the regime.